The role of the Middle Turkic writing records in determining the characteristics of the area of language systems and common symbol (Eurasian Journal of Philology Science and Education, 2016)
The article is considered the development of modern Turkic languages, namely, the historical phonetic process of sound change of phonemes and systematization of sounds is determined by the historical formation of the phonetic laws. From the point of view the grammar system is defined the word phrases, historical and semantic structure of the root in proving the historical development and the formation of grammatical categories and forms of Turkic languages.
Keywords: Comparative-historical study; common Turkicalphabet; Turkic peoples; grammatical features; sound system.